Nanocarriers in Tuberculosis Treatment: Challenges and Delivery Strategies - Mahesh Kumar; Tarun Virmani; Girish Kumar; Rohitas Deshmukh; Ashwani Sharma; Sofia Duarte; Pedro Brandão; Pedro Fonte (MDPI AG, 2023)
The World Health Organization identifies tuberculosis (TB), caused by Mycobacterium tuberculosis, as a leading infectious killer. Although conventional treatments for TB exist, they come with challenges such as a heavy pill regimen, prolonged treatment duration, and a strict schedule, leading to multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains. The rise of MDR strains endangers future TB control. Despite these concerns, the hunt for an efficient treatment continues. One breakthrough has been the use of nanotechnology in medicines, presenting a novel approach for TB treatment. Nanocarriers, such as lipid nanoparticles, nanosuspensions, liposomes, and polymeric micelles, facilitate targeted delivery of anti-TB drugs. The benefits of nanocarriers include reduced drug doses, fewer side effects, improved drug solubility, better bioavailability, and improved patient compliance, speeding up recovery. Additionally, nanocarriers can be made even more targeted by linking them with ligands such as mannose or hyaluronic acid. This review explores these innovative TB treatments, including studies on nanocarriers containing anti-TB drugs and related patents.